Behaviors used by neonatologists in face of patients without curative possibilities in Santa Catarina in 2021 (Research, Society and Development, 2022)
Objective: The aim of this study was avaliate the conduct of neonatologists in the Neonatal Intensive Care Unit (NICU), facing newborns without curative possibilities, comparing with the sociodemographic characteristics of professionals and the existence of guidelines in the NICU, in Santa Catarina (SC) in 2021. Methods: This is a cross-sectional study carried out with neonatologists from the NICU of SC, from March to June 2021. Data collection was performed through an electronic questionnaire, built on a Likert scale (n=110). Spearman's Correlation Test was used to determine whether the variable knowledge about neonatal palliative care differed statistically according to the views, practices and sociodemographic characteristics of the research participants, achieving a significance level of p ≤ 0.05. Results: The total number of participants, 100% affirmed need mandatory training PC training during medical residency, 85.5% revealed differences in the application of PC, 46.4% considered there was no favorable NICU environment for the provision of PC, 70% claimed that the participation of parents in decisions about PC does not happened. The use of guidelines in the NICU (Rho= -0.332) and confidence in the application of the PC (Rho= -0.375) showed a negative correlation with the frequency of application of the PC. Conclusion: The frequency of PC application influenced in trust level, the use of guidelines and less differences in the provision of this care. Furthermore, the lack of trust, guidelines and a NICU with an adequate environment confirmed the need for measures to fill in the gaps in neonatal palliative care.